Segurança no trabalho de preparo de calda no tanque de 2.000L do turbopulverizador com formulações líquidas de agrotóxicos registradas para a cultura de goiaba - Tácio, Matheus Bellini; de Oliveira, Maurício Leite; Neto, Joaquim Gonçalves Machado [UNESP] (My University, 2010)
Pure formulations are manipulated during the mixing of pesticide sprayer, involving elevated exposure of workers. The aim was to quantify the dermal and respiratory exposures at ten day liquid formulations of pesticides registered for the guava orchards in the activity of mixing the spray and loading to fill ten tank of 2,000 L of air-assisted sprayer, and distribution of dermal exposure in body parts of the worker; evaluate the efficiency of two sets of personal protective clothing water-repellent to control dermal exposure, and classify the activities with ten formulations in safe or unsafe, with and without the use of personal protective clothing, and determine the exposure control need and the number of mixing of pesticides safe. Dermal exposure in the activity of mixing the spray is 13.35 mL formulation/day and respiratory, 0, 000,153 ml. In this activity of mixing the spray, the worker's hands are the body parts most at exposure, with 70.6% of dermal exposure. The efficiency of the set Agro Light is 92.8% of the dermal exposure daily and Kit Tratorizado, 94.2%. The dermal exposure not-controlled by sets of personal protective equipment are distributed in different parts of the body of the worker. The activities of mixing the spray with ten liquid formulations of pesticides registered in the guava orchard are unsafe for the worker. With the use of sets of personal protective clothing, only the activity of mixing the spray with PROVADO insecticide (imidacloprid 200 g / L) is safe. For unsafe working conditions, the exposure control need ranging from 73.8 to 100% (no protection), 26.9 to 99.7% (Agro Light) and 9.4 to 99.6% (Kit Tratorizado). The number of mixing of pesticides safe is 0 tanks / day without protection, from 0 to 5 or 7 (Agro Light) or to 6, 7 or 9 (Kit Tratorizado).
Work safety during the mixing of pesticide of the 2.000L air-assisted sprayer tank wiht pesticide liquid formulations registered in guava orchards
Keywords: Dermal exposure; Guava; Pesticide; Respiratory exposure